FAMILY AND ALZHEIMER’S DISEASE. A CUALITATIVE APPROACH - Algado, Mª Teresa; Basterra, Ángel; Garrigós, J. Ignacio (Anales de Psicología / Annals of Psychology)
This work analyzes, from a cualitative perspective, the consequences to take care Alzheimer`s diseased. Family health care affects the personal and familiar life, and, even, the social relationship. From this work we want to expose that Alzheimer`s disease is a medical problem as well as a familiar and social one, who needs much more attention.